2016
DOI: 10.1002/chem.201605329
|View full text |Cite
|
Sign up to set email alerts
|

13C MR Hyperpolarization of Lactate by Using ParaHydrogen and Metabolic Transformation in Vitro

Abstract: Abstract:Hyperpolarization of the 13C magnetic resonance signal of L-[1-13C]Lactate has been obtained using the chemically based, cost-effective method named ParaHydrogen Induced Polarization by means of Side Arm Hydrogenation (PHIP-SAH). Two ester derivatives of lactate have been tested and the factors that determine the polarization level on the product have been investigated into details. The metabolic conversion of hyperpolarized L-[1-13C]Lactate into Pyruvate has been observed in vitro using lactate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 42 publications
2
79
0
2
Order By: Relevance
“…[5] An alternative and simple route to nuclear spin polarization involves the addition of singlet-state-based parahydrogen (p-H 2 )t oa nu nsaturated center, collectively termed parahydrogen-induced polarization (PHIP). [8] In 2009, the PHIP technique termed signal amplification by reversible exchange (SABRE) allowed access to hyperpolarized substrates without changing their chemical identity. [7] Recently,t he use of cleavable,u nsaturated molecular tags, including propargyl esters,h as broadened the scope of the PHIP method to include access to pyruvate,acetate,and even lactate for the monitoring of metabolism in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…[5] An alternative and simple route to nuclear spin polarization involves the addition of singlet-state-based parahydrogen (p-H 2 )t oa nu nsaturated center, collectively termed parahydrogen-induced polarization (PHIP). [8] In 2009, the PHIP technique termed signal amplification by reversible exchange (SABRE) allowed access to hyperpolarized substrates without changing their chemical identity. [7] Recently,t he use of cleavable,u nsaturated molecular tags, including propargyl esters,h as broadened the scope of the PHIP method to include access to pyruvate,acetate,and even lactate for the monitoring of metabolism in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of the parahydrogen spin order to 13 C net magnetization takes place though very small, long range J‐couplings and this transfer is efficiently pursued by means of a properly designed magnetic field cycle (MFC), i. e. a polarization transfer method that can facilitate hyperpolarization transfer through long distance spins . The PHIP‐SAH method appears of general applicability and it has been successfully tested to obtain 13 C HP acetate, [1‐ 13 C]lactate and [1‐ 13 C]‐pyruvate.…”
Section: Introductionmentioning
confidence: 99%
“…Cleavage of the precursor molecule leads to hyperpolarized metabolites. In the case of lactate, it was demonstrated that, after the polarization procedure, lactate can enzymatically be converted into pyruvate . So far, the most successful approach of hyperpolarizing metabolites with para ‐hydrogen relies on a field cycling technique, for which 13 C polarization values of about 5 % have been experimentally demonstrated in highly concentrated solutions of acetate and pyruvate .…”
Section: Figurementioning
confidence: 99%